Characterisation of sharp edges Schottky contacts with nanostructure film - Mohd. Azol, Mas Elyza (2015)
Studies investigating nanostructure on Schottky diode reported that sharp edge of nanostructures produces high electric field. It has been suggested that high electric field improve gas sensing performance on reverse biased mode. Electric field also promotes the ionisation of gas molecule thus improving sensing performance. Thus, the author aims to investigate the effect of sharp edges Schottky contacts towards electric field and Schottky diode performance. This can be achieved through simulation and experiment. COMSOL Multiphysics was used to model Schottky contact shape: circular-, hexagon- and star-shape. Star-shape Schottky contact produced 2.79 x 109 V/m total electric field followed by hexagon- and circularshape. Acute angle of star-shape at 72° contributed higher electric field 4 x 104 V/m than obtuse angle. After that, sensing layer of Schottky diode was fabricated by using Radio Frequency (RF) magnetron sputtering to deposit Zinc Oxide (ZnO) and Titanium dioxide (TiO2). In addition, highly potential material Carbon Nanotubes (CNTs) were investigated along these materials, which were sensitive towards gas sensing. Platinum was chosen as Schottky contact metal since it is known as a good catalytic metal to help absorption of hydrogen gas into the sensing layer. Finally, the sharp edges Schottky contacts with nanostructure film devices were characterised. Series of current-voltage (I-V) characteristics were recorded using Keithley 2400 and temperature was varied from room temperature to 200°C towards 1% hydrogen gas in a vacuum chamber. Results show that hexagon-shape Pt/TiO2/Si Schottky diode gave better barrier height of 494 meV than circular-shape. Furthermore, the response shows that 0.3 mA current changes were observed at star-shape Pt/CNTs/Si Schottky diode based sensors in forward biased mode. On the other hand, 0.21 mA was observed at hexagon-shape Pt/CNTs/Si Schottky diode based sensor on reverse biased mode. This signifies that improvement can be made by tailoring the Schottky contact shape to increase the electric field for sensing purposes